Intersections between development and evolution in the classification of emotions. Issue 1 (2nd July 2012) - Clark, Jason A.; Moore, David; Moore, Chris
Abstract In this article, I use the example of emotions to illustrate how various concepts of homology can play a role in developmental psychology by showing how developmental and evolutionary approaches to the classification of psychological traits complement and constrain one another. In order to do this I argue against the "Standard Model" of emotional classification according to which basic and higher cognitive emotions belong to radically different classes of emotions. Neither developmental nor evolutionary considerations support the Standard Model, and a combined ontogenetic and phylogenetic approach presents a stronger case for the revision of this model than does either of these taken alone. Recent attempts to integrate developmental and evolutionary factors in the explanation of other psychological traits can guide research in these areas. I argue that a consideration of various neglected forms of homology that are closely tied to development resolves some outstanding problems in ontogenetic and phylogenetic classification of emotion. © 2012 Wiley Periodicals, Inc. Dev Psychobiol 55: 67–75, 2013.